Characterization of Fatty Acid Metabolism in Lung Adenocarcinoma - Wang, Suyu; Chen, Aona; Zhu, Wanli; Feng, Di; Wei, Juan; Li, Quanfu; Shi, Xuan; Lv, Xin; Liu, Meiyun (Frontiers in Genetics, 2022)
Background: Lung adenocarcinoma (LUAD) is the most common subtype of non-small cell lung cancer. Fatty acid metabolism takes part in malignancy progression. However, the roles fatty acid metabolism play in LUAD are still unclear. Methods: The transcriptomic and clinical data of LUAD patients from the Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases was extracted. ssGSEA, WGCNA, univariable Cox regression and LASSO Cox regression analyses were used to identify the fatty acid metabolism-related genes which influenced overall survival (OS) and build a fatty acid-related risk score (FARS) model. A nomogram was established based on FARS and other clinicopathological features and ROC and calibration plots were used to validate the prediction accuracy. Tumor microenvironment (TME) of patients with high and low FARS was compared. Results: 38 genes were identified to be independently related to survival outcome and put into a FARS model. High FARS patients exhibited significant worse OS. The nomogram included FARS and pathological Stage, and the AUC of the nomogram predicting 1-, 2-, 3-, 4- and 5-year OS was 0.789, 0.807, 0.798, 0.809, 0.753 respectively. Calibration plots also indicated good accuracy. What’s more, the samples of the high FARS had higher expression of PDL1. Conclusion: We constructed a FARS model which could accurately predict survival outcome of the LUAD patients. The genes of FARS are related to tumor microenvironment and patients with high FARS can potentially benefit more from anti-PD1/PDL1 immunotherapy. In addition, the mechanisms of the genes in the FARS affecting prognosis are worthy of further research to develop new gene-targeted drugs.